2018
DOI: 10.1109/tvcg.2017.2750689
|View full text |Cite
|
Sign up to set email alerts
|

A Vector Field Design Approach to Animated Transitions

Abstract: Animated transitions can be effective in explaining and exploring a small number of visualizations where there are drastic changes in the scene over a short interval of time. This is especially true if data elements cannot be visually distinguished by other means. Current research in animated transitions has mainly focused on linear transitions (all elements follow straight line paths) or enhancing coordinated motion through bundling of linear trajectories. In this paper, we introduce animated transition desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Of the remaining four publications, two used Canvas and two used WebGL. For example, Wang et al [38] "used SVG for visualizing the animations, as it is easier to operate on the SVG elements and the efficiency of SVG is acceptable for our project". On the other hand, Jo et al [22] wrote their application with "the HTML5 Canvas API to support visualizing tens of thousands of nodes and edges."…”
Section: Svgs In Information Visualization Researchmentioning
confidence: 99%
“…Of the remaining four publications, two used Canvas and two used WebGL. For example, Wang et al [38] "used SVG for visualizing the animations, as it is easier to operate on the SVG elements and the efficiency of SVG is acceptable for our project". On the other hand, Jo et al [22] wrote their application with "the HTML5 Canvas API to support visualizing tens of thousands of nodes and edges."…”
Section: Svgs In Information Visualization Researchmentioning
confidence: 99%
“…However, when going beyond just presenting the changes to assisting in highlevel analysis tasks (e.g., tracking temporal trends, comparing temporal changes in multiple objects, etc. ), animation encounters many challenges [27], especially keeping consistency over frames, e.g., keeping objects in the same group moving consistently [28], or applying smooth transitions between frames [29]. Without careful design, animation can be used poorly, because people have trouble tracking more than four moving objects at a time [30].…”
Section: Temporal Data Visualizationmentioning
confidence: 99%
“…Dragicevic et al [DBJ * 11] compared time distortion methods, such as slow-in / slow-out and fast-in / fast-out, and found that slow-in / slow-out enabled users to better track visual objects. Other studies concern improving data point trajectory paths using bundling [DCZL15] or vector field [WASQ18] techniques. Taking this prior work into account, here we develop both elaborate multi-stage transitions and simpler variants for comparison.…”
Section: Related Workmentioning
confidence: 99%
“…Animation can help viewers track changes and stay oriented across transitions between related statistical graphics [RMC91, Gon96, BB99, HR07], with research to‐date primarily focused on transitions in response to filtering, time steps, changing variables, or adjusting visual encodings [HR07, RFF∗08, CDF14, DBJ∗11, WASQ18]. However, visual analysis regularly involves summarizing groups of data using aggregation operations such as count, sum, and average.…”
Section: Introductionmentioning
confidence: 99%